Tingkat Efektivitas Online Marketing Untuk UMKM Semasa Pandemi Covid-19 - Tiberias Krisgaharu; Bisma Oscar Perdana Kusuma (EXERO : Journal of Research in Business and Economics, 2021)
This paper aims to determine the effect of the COVID-19 pandemic on MSMEs in Indonesia and to find out the potential use of digital marketing to develop MSME businesses, to find out digital marketing strategies that MSMEs can do to develop their business during the COVID-19 pandemic and to determine the effectiveness of digital marketing strategies. this, as well as to find out the influence that is obtained by MSMEs from digital marketing that is carried out. Through this research, the author tries to analyze the effectiveness of online marketing for MSMEs during the COVID-19 pandemic to answer the problems that exist caused by the COVID-19 pandemic, especially those related to MSME business actors. The data and information that support this writing were obtained by conducting a literature study through relevant sources, namely theses or final assignments, reports, scientific journals, books, and the latest news. At this writing, it was found that with the COVID-19 pandemic, there was a change in consumer behavior which led to an increase in the potential of digital marketing. With this, it was found that there are many digital marketing strategies that can be carried out by MSME actors. This digital marketing strategy can be used by MSME actors to strengthen their position in the era of the COVID-19 pandemic.